2005
DOI: 10.1108/00070700510629760
|View full text |Cite
|
Sign up to set email alerts
|

Subjective norms, attitudes and intentions of Finnish consumers in buying organic food

Abstract: Foster, (2005),"Exploring the gap between attitudes and behaviour: Understanding why consumers buy or do not buy organic food", If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

75
620
12
28

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 785 publications
(812 citation statements)
references
References 31 publications
75
620
12
28
Order By: Relevance
“…Recently, a study in the organic sector in Germany reported R 2 values of 46% for attitude and 42% for purchasing behaviour 18 . Studies using covariance-based methods in the organic sector report R 2 scores between 13% and 37% for attitude, 15% and 56% for intention to purchase, and 48% and 82% for behaviour 47,52,53 . Considering these values, the model in Chile poorly explains consumer attitude.…”
Section: Causal Model Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study in the organic sector in Germany reported R 2 values of 46% for attitude and 42% for purchasing behaviour 18 . Studies using covariance-based methods in the organic sector report R 2 scores between 13% and 37% for attitude, 15% and 56% for intention to purchase, and 48% and 82% for behaviour 47,52,53 . Considering these values, the model in Chile poorly explains consumer attitude.…”
Section: Causal Model Estimationmentioning
confidence: 99%
“…Some researchers have found that the relationship between intentions of buying organic food and the behaviour is positive and significant [52][53][54] . It is thus assumed that consumer intention will also influence stated behaviour of organic food consumption in Germany and Chile.…”
mentioning
confidence: 99%
“…The multicomponent view of attitude assumes that evaluations are influenced by cognition as well as affect (Ajzen, 2001). In the context of organic food purchases, Magnusson et al (2001Magnusson et al ( , 2003 and Tarkiainen and Sundqvist (2005) find attitude to explain purchase intention. Attitude towards minimally processed Ecolabelled food products was found positively affecting the perception of perceived quality of minimally processed vegetable products (Nassivera & Sillani, 2015).…”
Section: Attitude Towards Minimally Processed Food Productsmentioning
confidence: 99%
“…Dans une méta-analyse basée sur 185 études indépendantes, Armitage et Conner (2001) trouvent que la TCP permet de restituer, en moyenne, 39 % de la variance des intentions et 27 % de celle du comportement. Il est intéressant de noter que la TCP est assez naturellement mobilisée pour prédire des consommations alimentaires marquées par une certaine idéologie politique comme l'achat de produits équitables (Shaw & Shiu, 2002 ;Ozcaglar-Toulouse et al, 2006), de produits écologiques (Sparks & Shepherd, 1992 ;Kalafatis et al, 1999), de produits issus de l'agriculture biologique (Tarkiainen & Sundqvist, 2005 ;Lodorfos & Dennis, 2008, voir Aertsens et al, 2009, pour une revue) ou encore l'intention d'adhérer à une AMAP (Bertrandias & Pernin, 2010 -l'identité de soi (Sparks & Shepherd, 1992, voir Rise et al, 2010, pour une méta-analyse) qui renvoie à la question « qui suis-je ? ».…”
Section: La Théorie Du Comportement Planifié éTendueunclassified